The impact of initiation timing of continuous renal replacement therapy on outcomes in critically ill patients with acute kidney injury a retrospective study from the MIMIC-IV database - Mangsuer Nuermaimaiti; Meiping Wang; Ran Lou; Nan Wang; Quan Si; Tingting Wang; Li Jiang (Scientific Reports)
Abstract Acute kidney injury (AKI) is common in critically ill patients, optimal timing for initiation of renal replacement therapy (RRT) for AKI but without life-threatening indications is unclear. A retrospective study was performed using the medical information mart for intensive care (MIMIC-IV), including AKI patients identified based on kidney disease improving global outcomes (KDIGO) definition. The time to initiate CRRT was defined as the interval from first diagnosis of AKI to the initiation of CRRT, analyzed as a continuous variable. The primary outcome was 28-day mortality, restricted cubic splines (RCS) to assess the relationship between CRRT initiation timing intervals and clinical outcomes. The study included 673 patients, with a 28-day mortality rate of 38.78%. RCS analysis revealed no significant association between variations in CRRT timing intervals and 28-day mortality (P > 0.05). In the subgroup of patients with non-renal SOFA scores < 8, observed an increase in 28 day mortality (OR 1.011 [95% CI 1.001–1.021], P < 0.05), along with a greater likelihood of reduced 28-day CRRT, mechanical ventilation (MV), and ICU-free days for each 1-h delay in CRRT initiation (OR − 0.037 [95% CI − 0.064 to − 0.010], P < 0.05; OR − 0.051 [95% CI − 0.078 to − 0.024], P < 0.05; OR − 0.056 [95% CI − 0.082 to − 0.003], P < 0.05). The findings indicate that while no significant relationship exists between mortality and the timing of CRRT initiation, patients with lower non-renal SOFA scores who initiate RRT promptly may experience improved clinical outcomes. Further exploration and validation require the adoption of novel research methodologies and more pertinent clinical studies.